BIOPROSPECTING OF INDIGENOUS PLANT Syzygium Cumini L. Skells AGAINST VACTERIA PATHOGENS: english - Muhammad Faizal Fathurrohim (JURNAL BIOSENSE, 2026)
Antimicrobial testing is a test to measure the ability of a substance to inhibit bacterial growth. The purpose of this study was to determine the inhibitory power of jamblang fruit extract against pathogenic bacteria. The research method used 96% ethanol extract of jamblang fruit and an inhibition zone test was carried out on 4 pathogenic bacteria, then a phytochemical test was carried out on the jamblang fruit extract. The results showed that jamblang fruit extract could inhibit the growth of pathogenic bacteria MRSA (28 mm) and S. typhi (30 mm), while L. monocytogenes and V. cholerae did not show an inhibition zone. Several bioactive compounds were successfully identified from jamblang fruit extract, namely phenolics, flavonoids, and tannins. So jamblang fruit has the potential as an antibacterial.